Comparative analysis of the cytotoxic effect of 7-prenyloxycoumarin compounds and herniarin on MCF-7 cell line - Seyed Hadi Mousavi; Atiyeh-Sadat Davari; Mehrdad Iranshahi; Sarvenaz Sabouri-Rad; Zahra Tayarani Najaran (Mashhad University of Medical Sciences, 2015)
Objectives: 7-prenyloxycoumarins are a group of secondary metabolites that are found mainly in plants belonging to the Rutaceae and Umbelliferae families. This study was designed to evaluate and compare the cytotoxic and apoptotic activity of 7-prenyloxycoumarin compounds and herniarin on MCF-7, a breast carcinoma cell line. Materials and Methods: Cells were cultured in RPMI medium and incubated with different concentrations of auraptene, herniarin, umbelliferone, and umbelliprenin. Cell viability was quantified by MTT assay. Apoptotic cells were determined using propidium iodide staining of DNA fragmentation by flow cytometry (sub-G1peak). Bax protein expression was detected by western blot to investigate the underlying mechanism. Results: Doses which induced 50% cell growth inhibition (IC50) against MCF-7 cells with auraptene, herniarin, umbelliferone, and umbelliprenin were calculated (59.7, 207.6, 476.3, and 73.4 µM), respectively. Auraptene induced a sub-G1 peak in the flow cytometry histogram of treated cells compared to control cells, and DNA fragmentation suggested the induction of apoptosis. Western blot analysis showed that auraptene significantly up-regulated Bax expression in MCF-7 cells compared to untreated controls. Conclusion: Auraptene exerts cytotoxic and apoptotic effects in breast carcinoma cell line and can be considered for further mechanistic evaluations in human cancer cells. These results candidate auraptene for further studies to evaluate its biosafety and anti-cancer effects.